Ileal Ureter Replacement: Foundations, Robotic Advances, Horizons - Noah N. Nigro; Karen M. Doersch; Sasha J. Vereecken; Carter Niedert; Rohan G. Bhalla; Brian J. Flynn (Uro, 2025)
The use of ileum for ureteral reconstruction was first described in 1906. Since then, its utilization has evolved considerably. Early in the history of ileal ureters, urologists were limited by a lack of familiarity with bowel harvesting and handling. The popularization of ileal conduits for urinary diversions, however, allowed urologists to familiarize themselves with the use of ileum and paved the way for broader applications. With the emergence of laparoscopy and, later, robotic-assisted surgery, the application of ileal ureteral replacement expanded the capabilities of reconstructive urologists. This article describes the historical development of surgical techniques for ileal ureter replacement and the integration of new technologies aiding in improved outcomes, and anticipates potential future directions. In contemporary practice, robotic-assisted ileal ureteral replacement is used in cases of extensive ureteral obstruction or damage. Advantages of the robotic platform include reduced blood loss, shorter recovery time and hospital length of stay, and superior operative ergonomics. Although robotic ileal ureter replacement is a complex and challenging surgery with notable complications, studies have demonstrated the efficacy and safety of this technique in patients with an otherwise end-stage ureter. In addition, the robotic approach has provided urologists the ability to conduct complex reconstructive surgeries including bilateral ureteral replacement in conjunction with bladder augmentation or a urinary diversion. Long-term studies and continued innovation are necessary to further improve the surgical techniques, outcomes, and scope of ileal ureter reconstruction.